End‐to‐end elasticity control of cloud‐network slices. Issue 4 (6th June 2019) - Medeiros, Alisson; Neto, Augusto; Sampaio, Silvio; Pasquini, Rafael; Baliosian, Javier
Abstract : The design of efficient elasticity control mechanisms for dynamic resource allocation is crucial to increase the efficiency of future cloud‐network slice‐defined systems. Current elasticity control mechanisms proposed for cloud‐ or network‐slicing, only consider cloud‐ or network‐type resources respectively. In this paper, we introduce the elaSticity in cLOud‐neTwork Slices ( SLOTS ) which aims to extend the horizontal elasticity control to multi‐providers scenarios in an end‐to‐end fashion, as well as to provide a novel vertical elasticity mechanism to deal with critical insufficiency of resources by harvesting underused resources on other slices. Finally, we present a preliminary assessment of the SLOTS prototype in a real testbed, revealing outcomes that suggest the viability of the proposal.